Audit Sistem E-Learning pada Universitas ABC Menggunakan Framework COBIT 5 - Domain MEA (Monitoring, Evaluate and Assess) - Putra, Kevin; Wahyuningtyas, Emmy (Melek IT : Information Technology Journal, 2023)
Information technology (IT) has a very important role in an institution, both educational and non-educational to support the learning function within the institution. If the use of IT has been going well and is able to integrate well, then IT is able to encourage an increase in performance within the institution. For this reason, IT management is needed so that it can be utilized properly. ABC University implements E-Learning as an online learning medium, but its implementation still requires evaluation. Assess the level of capability and prepare recommendations for IT management that do not meet the standards. The evaluation standard usd is COBIT 5 domain Monitor, Evaluate and Assess (MEA) which focuses on supervision, assessment and regulatory compliance of the entire IT system. COBIT 5 is a framework that has a broad and more detailed spectrum of IT processes.  In this study, researchers took research to audit E-Learning from ABC University in order to determine the maturity of the system as well as monitor and evaluate to comply with the COBIT 5 MEA domain framework. From this research, the researcher can give some recommendations after auditing and calculating each domain, sub domain and gap analysis. In accordance with the existing level conditions, every recommendation given by the university can be realized by 95%. This recommendation is made in accordance with the target of achieving maturity level is 2 while currently the level achieved is 1.